Work Life Integration: Tool to Success for Organisations (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Organizations focus upon increased revenue generated by its employees,  competitive workforce and employee dedication for achieving its strate gic goals in order to meet the challenges of 21st century. Work–life bal ance is a concept including proper prioritizing between “workaholics”  (career and ambition) on the one hand and “lifestyle” (Health, pleasure,  leisure, family and spiritual development) on the other. With the increase  in the proportion of dual earner families and the kind of life style finance  people are having work life conflicts are inevitable. There is a need for  organizations to adopt human resource strategies and policies that ac commodate the work-life needs of a diverse workforce in the current busi ness environment. The findings reveal that work-life balance is both im portant for the organization and for its employee’s particularly in current  dynamic organizational scenarios. It helps the organization to improve  productivity, efficiency, competitiveness, morale and hence gain a com petitive edge. Similarly employees are benefited from work-life balance  initiatives through increased motivation to work, enhanced satisfaction,  empowerment and ultimately more commitment to the organization.
Keywords: Work life balance; organization; conflicts; Policies